Ferroptosis: a novel perspective on tumor immunotherapy - Xu, Yuan; Ge, Mingpai; Xu, Yuqing; Yin, Kai (Frontiers in Immunology, 2025)
Ferroptosis is a novel form of programmed cell death characterized by iron-dependent accumulation of reactive oxygen species (ROS) and lipid peroxidation. The execution of ferroptosis is intricately linked to both iron and lipid metabolism. Intriguingly, iron and lipid metabolism are also pivotal for maintaining the physiological function of immune cells. Research has revealed that ferroptosis can potentiate the immunogenicity of tumor cells and engage in intricate interactions with immune cells. Certain ferroptosis inducers have the capacity to augment the efficacy of immunotherapy by modulating the tumor immune microenvironment. Ferroptosis holds immense potential in cancer immunotherapy and is anticipated to emerge as a novel therapeutic target in the future landscape of cancer treatment. In this review, we primarily delineate the ferroptosis signaling pathways and metabolic processes pertinent to immune cells, and further summarize the roles of ferroptosis in tumor-infiltrating immune cells. Ultimately, we anticipate further elucidation of the mechanisms of ferroptosis in immunotherapy and envision that strategies targeting ferroptosis and immunotherapy will be expeditiously applied in clinical oncology practice.